BENTUK PEMBIAYAAN MUSYARAKAH MUTANAQISHAH DI LEMBAGA KEUANGAN SYARIAH - Solihin, Dadin; Suarsa, Abin (2019)
Financing with Islamic banks or Islamic Financial Institutions (LKS) for business partners, is one of the financing supports for goods, services, and business, including home ownership, production machinery, assets, or other productive inventories. This study analyzes the concept of the implementation of mushārakah mutanāqishah (MMQ) financing and the (term) mode of mushārakah mutanāqishah financing in LKS. The purpose of the study, essentially looking for scientific relevance of the three problems that are the object of study, both from the implementative dimension, as well as normative. Mushārakah mutanāqishah is a hybrid contract between the mushārakah and ijārah contracts. This term is also implementatively less popular. The study was conducted in a descriptive qualitative manner on MMQ financing products in LKS, then analyzed in a normative juridical manner based on DSN-MUI Fatwa and applicable regulations in Indonesia. Data is sourced from various literature, regulations, interviews, and other data relevant with the research material. Reviewing concept of the implementing mushārakah mutanāqishah financing in LKS, this has only been applied in a number of products, such as applied for home ownership financing (PPR iB products), indent home ownership financing (PPR-Indent iB products), used for business cooperation in goods physical (inventory), such as for financing machinery, manufacturing equipment, vehicles, as well as other physical objects that are productive and profit oriented, but also developed for the financing of commercial business activities carried out various forms of business in accordance with the sharia principles including principles of buying and selling, profit sharing and leasing. Whereas regarding term of mushārakah mutanāqishah financing, stakeholders can use one the eight forms of mushārakah mutanāqishah financing as needed by taking into account dimensions shirkah capital (portion) of the bank, customer capital, profit sharing method, return method bank portion funds, gradual promise transfer of portions, term of financing period, and type allocation of financing.